1997
DOI: 10.1063/1.365620
|View full text |Cite
|
Sign up to set email alerts
|

Oxygen as a surfactant in the growth of giant magnetoresistance spin valves

Abstract: We have found a novel method for increasing the giant magnetoresistance (GMR) of Co/Cu spin valves with the use of oxygen. Surprisingly, spin valves with the largest GMR are not produced in the best vacuum. Introducing 5×10−9 Torr (7×10−7 Pa) into our ultrahigh vacuum deposition chamber during spin-valve growth increases the GMR, decreases the ferromagnetic coupling between magnetic layers, and decreases the sheet resistance of the spin valves. It appears that the oxygen may act as a surfactant during film gro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
47
2

Year Published

2001
2001
2020
2020

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 197 publications
(56 citation statements)
references
References 24 publications
6
47
2
Order By: Relevance
“…The calculations were performed assuming a bulk scattering with γ = 0.7eV that gives a saturation resistivity of 23µΩcm and a GMR of 16% in agreement with experimental data by Egelhoff et al 91,93 As is seen from Fig.34a, for the parallel (P) configuration the local conductivity of the Co layers is much higher for the majority spins than for the minority spins, which reflects the spin-dependent conductivity in the bulk Co (see Fig.31b at E=E F ). The local conductivities σ Cu in the Cu layers are higher than those in the Co layers and are different for different spins.…”
mentioning
confidence: 96%
See 1 more Smart Citation
“…The calculations were performed assuming a bulk scattering with γ = 0.7eV that gives a saturation resistivity of 23µΩcm and a GMR of 16% in agreement with experimental data by Egelhoff et al 91,93 As is seen from Fig.34a, for the parallel (P) configuration the local conductivity of the Co layers is much higher for the majority spins than for the minority spins, which reflects the spin-dependent conductivity in the bulk Co (see Fig.31b at E=E F ). The local conductivities σ Cu in the Cu layers are higher than those in the Co layers and are different for different spins.…”
mentioning
confidence: 96%
“…Specular scattering of electrons at Co/CoO interfaces was also suggested to be the reason for the enhancement of GMR by up to 17% at room temperature, obtained in bottom spin valves of the type NiO/Co/Cu/Co, in which the top Co layer was slightly oxidized. 91,90 Sugita et al 92 regarded the high magnitude of GMR of 28% obtained in an epitaxially-grown symmetric spin valve with an α- The importance of overlayers deposited at the top outer boundary of the NiO/Co/Cu/Co spin valve was demonstrated by Egelhoff et al 93 They found that the deposition of about 2 monolayers (ML) of Au, Ag, or Cu increases GMR, whereas the deposition of 2ML of Ta, Si, C, or Ni 80 Fe 20 decreases GMR. These results were interpreted by Egelhoff et al as evidence of enhanced specular scattering for the case of Au, Ag, and Cu, but suppressed specular scattering for the case of Ta, Si, C, and Ni 80 Fe 20 at the interface with Co.…”
Section: Outer Boundary Dependencementioning
confidence: 99%
“…The latter routine takes advantage of introduced vacuum interfaces, since the slowly growing film surface remains in the process atmosphere for the time of rotation until it passes the open shutter again. During this time, remnant gases adsorb at the surface and act as a surfactant during the sputter process, which leads to smoother film surfaces and thus higher interface qualities in multilayer systems 164,165 . Furthermore, it results in a more homogeneous film thickness across the substrate area by eliminating the deposition rate variation in the tangential direction of the carousel rotation, which is beneficial for larger sample sizes or arrays.…”
Section: Magnetic Thin Film Depositionmentioning
confidence: 99%
“…One of the promising ways to increase the giant magnetoresistance (GMR) is the use of specular reflection layers such as nano-oxide layers (NOLs) [1][2]. Although NOLs play an important role to enhance GMR effect in specular spin valves, the process control of the NOLs still remains a challenge for the applications in disk drives.…”
mentioning
confidence: 99%